MAKNA SIMBOLIS TRADISI SEDEKAH LAUT LONGKANGAN DI PANTAI BLADO KECAMATAN MUNJUNGAN, KABUPATEN TRENGGALEK - Nandiata Ayu Palanjuta; I Nyoman Ruja (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2022)
Sedekah Laut (Coastal Thanksgiving) is a tradition inherent to coastal communities or fishermen in Indonesia. The implementation of Sedekah Laut has a characteristic difference, both from ritual addressing to implementation. Although sea charity has the same purpose - as a means of giving thanks to God Almighty for the blessings that have been given- Munjungan people also has a Sedekah Laut tradition commonly called the Longkangan traditional ceremony. This tradition is routinely held annually in the month of Dzulkaidah on the Hijri or Sela calendar on the Javanese calendar. The implementation of tradition has a procession and symbolic meaning. This research aims to describe and analyze the implementation process and the meaning of Longkangan Ceremony tradition. This research used descriptive qualitative research methods with data collection techniques consisting of observation; interview; and documentation. Triangulation technique was also used to analyze the data that has been collected to obtain the validity of data according to the theory of symbolic interactionism according to George Herbert Mead and the concept of customary ceremonies according to Koentjaningrat. The results of study are the stages of Longkangan traditional ceremonies held twice in one day, the procession of Labuh Laut by Tumpeng Agung in the morning followed by officials and the Muspika (District-Level Executive Conference) as the patron of Munjungan District and the core ceremony at night followed by guests Breng Kidul. Each stage of this tradition procession also has a specific symbolic meaning. Hopefully, the historical manuscript of Longkangan traditional ceremonies can be recorded and can be studied by the younger generation, especially the Munjungan community.